Creation of a Continent Urinary Bladder Reservoir Vascularized by Omentum as a Possible Surgical Option for Canine Trigonal/Urethral Urothelial Carcinoma. Issue 3 (7th February 2022) - de Vlaming, Annemarieke; Mathews, Kyle G.; Hash, Jonathan A.; Keenihan, Erin K.; Sommer, Samantha; Borst, Luke; Vaden, Shelly L.
Abstract: Surgical procedures that maintain continence with minimal complication following resection of trigono-urethral urothelial carcinoma (UC) are limited in canines; therefore, palliative options are often pursued. A feasible tumor resection option may improve disease control and survival. The study's objective was to evaluate a continent urine reservoir created from the urinary bladder body and vascularized solely by omentum. We hypothesized that a viable urine reservoir could be created, and staged omentalization would provide improved vascularity. Nine normal female Beagles were randomized to one of three groups. Group A urinary bladders were transected cranial to the ureteral papillae to create a closed bladder vesicle which was concomitantly omentalized. Group B underwent omentalization two weeks prior to vesicle creation. Based on Group A and B results, Group C underwent neoureterocystostomy and omentalization followed by neoreservoir formation and tube cystostomy 2 weeks later. Serial ultrasounds and histopathology confirmed adequate omental neovascularization in Groups B and C with continent Group C neoreservoirs maintained for 2 months. Some pylectasia and ureteral dilation was documented in all Group C dogs at variable timepoints. Progressive hydroureteronephrosis developed in 2/6 kidneys. Transient azotemia was noted in only 1 Group C dog, although all developed treatable urinary tract infections. The sample size is limited, and the efficacy of this technique in providing disease control for UC is unknown. However, this novel option could allow for primary UC resection while providing continence and limiting complications. Postoperative local or systemic adjuvant therapy, ultrasonographic neoreservoir monitoring, and BRAF analysis would be indicated.